Funil de licenciamento de tecnologias: um modelo de gestão das etapas do processo de licenciamento de tecnologias para núcleos de inovação tecnológica das ICTs - Frank Gomes Bernardes (2021)
This study aims to research, propose, and test a conceptual model for the technology licensing process carried out by Scientific, Technological, and Innovation Institutions (STI) capable of assisting their Technology Transfer Offices (TTO) in managing the technology licensing process. This model encompasses the licensing stages, from the offer stage to the signing of the licensing agreement. Such proposal is justified by the need to increase the licensing performance indicators by the STI in Brazil since they are still incipient, according to FORMICT and FORTEC surveys. It was observed in this study that although Brazilian TTO have structured the management capacity and protection of Intellectual Property assets, the licensing results of these assets have not yet advanced to desirable levels. It also considers the following parameters: conversion rates of the offer stage of the technologies; conversion rates of the initial interaction with interested parties’ stage; conversion rates of the valuation stage; and conversion rates of the negotiation and contract formalization stage. A bibliographical review was conducted to elaborate the conceptual model and observation of the licensing processes carried out by the Coordination of Transference and Technological Innovation (CTIT), the TTO of the Federal University of Minas Gerais. The conceptual model was compared to the practices of five TTO of Brazilian STI chosen from the analysis of a classification model that compares the relationship between Intellectual Property (IP) and Technology Transfer (TT) number. The model was classified as in consolidated stage, according to the scale used for classification, and it was tested using CTIT data over a period of one year. The results of this work show that the proposed model can be used by TTO managers as a management tool for the licensing process and can help to define which competencies are necessary for structuring the licensing process in TTO. It was also identified that most TTO interviewed do not monitor process indicators of the stages listed in the model proposed in this work, but only a general indicator: the number of licensing agreement signed. Therefore, the suggestions of conversion rate indicators of the model developed in this work may help them in terms of improving the efficiency of their processes and identifying actions that generate more results. Furthermore, it was verified that the participation of the researcher inventor of the IP negotiated by the TTO is relevant to the licensing process.